The impact of entertainment screen time on sleep quality in Chinese and British adolescents: a moderated mediation model - Yang, Jingjing; Zhang, Shanshan (Frontiers in Psychology, 2026)
IntroductionAdolescents spend substantial time on media devices for entertainment. Sleep-a critical factor for physical and mental development-is increasingly insufficient among them. One of the contributing factors is the increased availability of technology. Despite previous studies indicating a link between screen time and sleep impairment, the psychological mechanisms underlying this relationship remain unclear. Additionally, the role of culture in this context is still ambiguous. This study aimed to investigate a conceptual framework elucidating how screen time influences sleep quality in adolescents through the mediation role of self-control, with country culture as a moderator.MethodsA total of 731 Chinese and British adolescents (mean age = 13.01 years, SD = 0.98) completed screen time scale, Children's Perceived Self-control Scale, and part of Youth Self-Rating Insomnia Scale (YSIS) at first. After the removal of values didn't meet criteria, 640 students (mean age = 12.93 years, SD =0.96) were retained for data analysis.ResultsThe results showed that (a) screen time was negatively associated with sleep quality (b = 0.22, p < 0.001); (b) self-control mediated the relationship between screen time and sleep quality; (c) country culture moderated the pathway from screen time to self-control (b = 0.50, p = 0.007), with the negative impact of screen time on self-control being stronger among British adolescents.DiscussionCollectively, these results suggest a potential mechanism through which entertainment screen time influences sleep quality and highlight the role of culture in this process. They underscore the importance of reducing entertainment screen time and enhancing parental control over screen time to address self-control deficits and, consequently, reduce sleep problems among adolescents.